Administrative innovations in Rajasthan - Mukerji, Mohan (ed.) (New Delhi, 1982)
This book is an excellent addition to the literature on state administration in India and is likely to motivate administrative reforms of a profound nature in other states of the country.
Keywords: Rajasthan